SEJARAH HUKUM ISLAM DI INDONESIA: DARI MASA KERAJAAN ISLAM SAMPAI INDONESIA MODERN - Eni Nurhidayah; Waskur (CV. Adiba Aisha Amira, 2024)
Islamic law is the basis for the formation of human behavior in Indonesia. The development of national law cannot be separated from the influence of Islamic law that lives in society. Research on Islamic law is very interesting to do. This library research is based on qualitative descriptive data on the history of the development of Islamic law. This study examines how the history of the development of Islamic law during the Islamic Kingdom, the colonial period, and the modern Indonesian period. The results of the study show that Islamic law in the archipelago has existed since the Islamic kingdom. The politics of king power are one of the main factors in the implementation of Islamic law. The Dutch colonialists initially accepted Islam but then Islamic law was clashed with customary law to weaken it so that Dutch law could be applied. During the Japanese occupation there was no policy that changed the validity of Islamic law, Japan focused on eliminating the remaining Dutch symbols. While in the modern Indonesian period, Islamic law is juxtaposed with positive law. The Indonesian Constitution recognizes three sources of law, namely western law, Islamic law, and customary law. Islamic law in the context of a new state can only be recognized after being made positive through legislation